1994
DOI: 10.1093/ajcp/101.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Mineralizing Pulmonary Elastosis in Chronic Cardiac Failure:“Endogenous Pneumoconiosis” Revisited

Abstract: The histopathology, ultrastructure, and clinicopathologic correlations in six patients with cardiac failure and iron encrustation of lung elastic tissue were examined at autopsy. Transmission electron microscopy (TEM) and energy dispersive x-ray analysis were applied to two cases. Of the group, five patients had cardiac failure due to systemic hypertension (4 patients), valvular disease (4 patients), or coronary atherosclerosis (4 patients). Biventricular failure in one patient was associated with sleep apnea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although the term iron encrustation is commonly applied, histochemical examination confirms the simultaneous presence of calcium phosphate as well. Thus the term "mineralizing pulmonary elastosis" is preferred over "iron encrustation of elastica" or "endogeneous pneumoconiosis" [ 8 ]. The pathogenesis of mineralizing elastosis is not known but it is speculated that the primary event is alveolar haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the term iron encrustation is commonly applied, histochemical examination confirms the simultaneous presence of calcium phosphate as well. Thus the term "mineralizing pulmonary elastosis" is preferred over "iron encrustation of elastica" or "endogeneous pneumoconiosis" [ 8 ]. The pathogenesis of mineralizing elastosis is not known but it is speculated that the primary event is alveolar haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it seems to us that sideroelastotic changes have been de scribed too seldom in published cases of PVOD (in 39%) to be considered a simple consequence of veno-occlusion. If the sideroelastotic vascular changes were really caused by disturbed perfusion and pressure in the partially oc cluded pulmonary venous tree, we would then expect them to occur more frequently in association with PVOD, especially as the right heart failure and abundant intraalveolar siderophages in the published cases demonstrate the severity of the pulmonary hypertension [6], Recently, Pai et al [27] examined the hypothesisoriginally proposed by Ceelen -that SP were to be caused by left cardiac failure [27], They concluded that SP is an infrequent accompaniment of cardiac disease and that at least in some of their cases the pulmonary changes were disproportionally severe in relation to the left cardiac dis ease. Moreover, a noteworthy veno-occlusion due to the elastic tissue degeneration and giant cell reaction could not be observed.…”
Section: Discussionmentioning
confidence: 99%